Dimensions of Cross-Cultural Communication and Validation - Farah Khadijah; Nadia Putri Salby; Nur Afiah Basir; Vania Darlene Pella; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study aims to analyze the influence of cross-cultural communication style dimensions—particularly the differences between high-context and low-context cultures—on the effectiveness of research instrument validation processes in achieving conceptual, semantic, and idiomatic equivalence. In addition, the study identifies key methodological challenges and sources of bias—such as content, method, and construct bias—that emerge in cross-cultural instrument validation, and evaluates mitigation strategies through the involvement of expert committees and translation techniques to ensure measurement invariance. The method employed is a qualitative article review using a descriptive–analytical approach to relevant literature. The analysis results indicate that differences in communication styles significantly affect meaning interpretation and may lead to misinterpretation, thereby hindering the achievement of equivalence. Major challenges include semantic mismatches, difficulties in transferring idiomatic expressions, and response bias. Mitigation strategies such as forward–back translation, the establishment of multidisciplinary expert committees, and the implementation of cognitive debriefing are shown to be crucial in navigating cultural complexity and ensuring measurement equivalence. The implications of this study emphasize the importance of adaptive and contextual approaches in cross-cultural instrument validation.